Evaluación de la remoción de amoxicilina mediante el uso de bentonita modificada por la técnica de delaminación (2020)
The main objective of this work was to evaluate the removal of amoxicillin by Fenton adsorption and oxidation techniques. As a starting material, for the two experiments a clay mineral (bentonite) was used, which was modified via delamination to increase its surface area and generate a meso and macroporous morphology, which allowed it to function as an adsorbent, catalyst and catalytic support for Fe, Cu and mixed oxides metals. It was determined that bentonite acted as a catalytic support and showed greater efficiency in the removal of amoxicillin by the Fenton type oxidation process, which in comparison to adsorption eliminated the antibiotic in less time. Additionally, the Fe catalyst was selected as the best, since it had the ability to convert the amoxicillin molecule to by-products and CO2 by 61%.